Persulfate-soil washing: The green use of persulfate electrochemically generated with diamond electrodes for depolluting soils - Silva, Karyn N.O.; Araújo, Karla C.F.; da Silva, Djalma R.; Martínez-Huitle, Carlos A. [UNESP]; Santos, Elisama V. dos [UNESP] (Elsevier, 2021)
Soil washing (SW) is a water-based approach that promotes a chemical-physical extraction as well as a separation process to eliminate or transfer the pollutants from soil to a liquid. Extraction step is often performed by using water and solvents in order to increase the solubility of pollutants and consequently, transfer efficiently them from soil to liquid phase. However, a contaminated effluent is generated and it should be treated. Therefore, in this study, persulfate solutions are used, for first time, as washing liquids. Persulfate was electrochemically generated in an electrochemical flow cell with boron-doped diamond (BDD) electrodes by applying different applied current densities in 0.5 M Na2SO4. After that, persulfate-soil washing approach was attained to remove dye from soil. Results indicated that, methyl orange (MO) was efficiently removed from soil when a solution of persulfate electrogenerated was used as soil washing (SW) procedure. Oxidation power of persulfate played a key role in the elimination of MO from soil as well as from water solutions, avoiding the generation of a high polluted effluent, which should be usually treated by using a post-treatment. Alternatively, this practice allows to produce/storage/transport persulfate which was electrochemically generated before remediation of contaminated soil and no significant volumes of organic solvents are used. Finally, environmental applicability of BDD electrodes as electrocatalytic material (persulfate production) as well as electrochemical sensor (MO in a range of 1–25 mg L−1, with 0.5 mg L−1 and 1.8 mg L−1 as limit of detection and limit of quantification, respectively) was possible, integrating eco-friendly approaches.
Keywords: Diamond electrode; Electrochemical sensor; Integrated electrochemical technologies; Persulfate; Soil washing